SENP1-SIRT3 axis mediates glycolytic reprogramming to suppress inflammation during Listeria monocytogenes infection - Yan Xiong; Yongliang Du; Feng Lin; Beibei Fu; Dong Guo; Zhou Sha; Rong Tian; Rui Yao; Lulu Wang; Zixuan Cong; Bohao Li; Xiaoyuan Lin; et al. (mBio)
ABSTRACT Listeria monocytogenes, a foodborne pathogen, has the ability to invade intestinal mucosal cells, undergo intracellular proliferation, activate host immune responses, and induce diseases such as colitis. We have demonstrated that sentrin-specific protease 1 (SENP1) functions as a protective gene in the host, suppressing the inflammatory response triggered by Listeria monocytogenes. The host’s SENP1-SIRT3 axis plays a critical role in regulating inflammation during Listeria monocytogenes infection. Our findings reveal that overexpression of SENP1, particularly under Listeria monocytogenes infection conditions (MOI = 20), effectively suppresses inflammation through modulation of glycolysis. Mechanistically, during Listeria monocytogenes infection, SENP1 accumulates in the mitochondria, facilitating the de-SUMOylation and activation of sirtuin 3 (SIRT3). Activated SIRT3 then regulates the deacetylation of pyruvate kinase M2 (PKM2), leading to a decrease in glycolytic intermediates, downregulation of glycolysis-related gene expression, and suppression of inflammation. Taken together, our study provides a deeper understanding of the mechanistic role of the SENP1-SIRT3 axis in the regulation of inflammation, offering novel insights, and strategies for the treatment and prevention of inflammatory diseases.IMPORTANCESentrin-specific protease 1 (SENP1)-sirtuin 3 (SIRT3) has never been reported in the regulation of bacteria-induced inflammation. Our study demonstrated that SENP1 acted as a protective factor against Listeria-induced inflammation by promoting SIRT3 activation and subsequent metabolic reprogramming. The SENP1-SIRT3 axis served not only as an essential signaling pathway for regulating mitochondrial metabolic responses to metabolic stress but also responds to bacterial invasion and plays a protective role in the organism. Our findings provide a basis for further research into targeting the SENP1-SIRT3 signaling pathway for the treatment of bacterial infections.